2004
DOI: 10.1002/yea.1067
|View full text |Cite
|
Sign up to set email alerts
|

SRE1 and SRE2 are two specific steroid‐responsive modules of Candida drug resistance gene 1 (CDR1) promoter

Abstract: CDR1 gene encoding an ATP-driven drug extrusion pump has been implicated in the development of azole-resistance in Candida albicans. Although the upregulation of CDR1 expression by various environmental factors has been documented, the molecular mechanism underlying such process is poorly understood. We have demonstrated earlier that the CDR1 promoter encompasses a large number of cisregulatory elements, presumably mediating its response to various drugs. In this study we have identified a novel steroid respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 49 publications
(75 reference statements)
3
41
0
Order By: Relevance
“…Since the hyphal form is responsible for tissue invasion, these reports imply that steroid hormones could act as cues for the virulence of C. albicans. The steroid signaling pathways are largely unknown in Candida, though steroid binding proteins exist in C. albicans (49). It was also observed that brief exposure of Candida cells to steroid hormones results in upregulation of the CDR1 gene (50).…”
Section: Cdr1p Transports Unconventional Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the hyphal form is responsible for tissue invasion, these reports imply that steroid hormones could act as cues for the virulence of C. albicans. The steroid signaling pathways are largely unknown in Candida, though steroid binding proteins exist in C. albicans (49). It was also observed that brief exposure of Candida cells to steroid hormones results in upregulation of the CDR1 gene (50).…”
Section: Cdr1p Transports Unconventional Moleculesmentioning
confidence: 99%
“…Since human steroid hormones induce CDR1 expression, its promoter was examined for the presence of steroid-responsive elements. The search resulted in the identification of a steroid-responsive region (SRR) comprising two distinct cis elements, SRE1 and SRE2, responsive to progesterone and progesterone and ␤-estradiol, respectively (49). Transcriptional analysis of Candida cells upon exposure to estrogen show the upregulation of CDR1 and CDR2, indicating a plausible connection with drug resistance (48).…”
Section: Regulation Of Cdr1 Transcriptionmentioning
confidence: 99%
“…In addition, another BRE (located between ÿ243 and ÿ234) and a 1 negative regulatory element (NRE) located within the ÿ289 region have been reported in CDR1 (Puri et al 1999;Gaur et al 2004). Finally, in the same gene, Karnani et al (2004) identified SRE1 and SRE2 (steroid response elements) between ÿ696 and ÿ521.…”
mentioning
confidence: 90%
“…RNA was stored at Ϫ80°C until use. [18][19][20][21] ] (Eurogentec), 3 l of 6.67 mM deoxynucleoside triphosphates (Roche), 1 l of 1 mM dCTP (Roche), 1.5 l of 1 mM cyanine 3 (Cy3)-dCTP or 1.5 l of 1 mM cyanine 5(Cy5)-dCTP (Amersham Biosciences), 4 l of 100 mM DTT (Invitrogen), 1 l of RNasin (20 to 40 U/l; Promega, Wallisellen, Switzerland), and diethyl pyrocarbonate-treated water to a volume of 40 l. The mixture was heated at 65°C for 5 min and cooled at 42°C for 5 min. The reverse transcription reaction was performed for 1 h at 42°C with 1 l of RNasin and 200 U of SuperScript II reverse transcriptase (Invitrogen).…”
Section: Tac1mentioning
confidence: 99%